2014
DOI: 10.1093/nar/gku718
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal globin gene expression is regulated by LYAR

Abstract: Human globin gene expression during development is modulated by transcription factors in a stage-dependent manner. However, the mechanisms controlling the process are still largely unknown. In this study, we found that a nuclear protein, LYAR (human homologue of mouse Ly-1 antibody reactive clone) directly interacted with the methyltransferase PRMT5 which triggers the histone H4 Arg3 symmetric dimethylation (H4R3me2s) mark. We found that PRMT5 binding on the proximal γ-promoter was LYAR-dependent. The LYAR DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Furthermore, seven linkage disequilibrium (LD) blocks containing 163 out of 271 common SNPs were identified in the 80-kb region ( Figure S1) 6 The analysis showed that SNPs rs368698783 was identified as a critical variant of ameliorating factors (HR ¼ 0.552, p ¼ 3.029 3 10 À14 ) after wellknown mutations at KLF1 and HBB in a ranking of Hazard ratio (Table 1). These results together with rs368698783 embedded within a highly conserved hexanucleotide LYAR-binding motif required for methylation-related g-globin gene silencing as previously described, 22 suggested that rs368698783-mediated epigenetic regulation of HbF elevation might be involved in the amelioration of b-thalassemia severity.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]supporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, seven linkage disequilibrium (LD) blocks containing 163 out of 271 common SNPs were identified in the 80-kb region ( Figure S1) 6 The analysis showed that SNPs rs368698783 was identified as a critical variant of ameliorating factors (HR ¼ 0.552, p ¼ 3.029 3 10 À14 ) after wellknown mutations at KLF1 and HBB in a ranking of Hazard ratio (Table 1). These results together with rs368698783 embedded within a highly conserved hexanucleotide LYAR-binding motif required for methylation-related g-globin gene silencing as previously described, 22 suggested that rs368698783-mediated epigenetic regulation of HbF elevation might be involved in the amelioration of b-thalassemia severity.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]supporting
confidence: 77%
“…22 However, the underlying mechanisms driving epigenetic regulation of Hb switching involved in ameliorating b-thalassemia severity are largely unclear.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]mentioning
confidence: 99%
“…Because there is no significant difference in the expression of these TALEs, it is presumed that TALE2a does not appear to have enough binding affinity to its target. TALE5 is designed to target the LYAR 40 site that is about 20 bp downstream of fetal-globin gene transcription start site, as mutation of LYAR often results in HPFH. 41 However, TALE5 may not have enough binding affinity even if it binds the LYAR site to displace the transcriptional machinery, and therefore downstream targeting will not be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to identify Myc target genes potentially important for the survival of Myc over-expressing cancer cells, we have identified a canonical E-Box at the gene core promoter of LYAR, and confirmed that N-Myc up-regulates LYAR expression by binding to its gene core promoter 4 . As a nucleolar and nuclear protein with zinc finger DNA-binding motifs, LYAR is known to suppress gene transcription by forming a protein complex with the protein arginine methyltransferase PRMT5 at target gene promoters 5 . We have confirmed through Affymetrix microarray gene expression study, gene set enrichment analysis and chromatin immunoprecipitation assay that LYAR considerably suppresses the transcription of oxidative stress genes, including SLC7A11, ULBP1, HMOX1 and CHAC1 4 .…”
supporting
confidence: 57%